PENGEMBANGAN SPIRITUALITAS MELALUI LAYANAN BIMBINGAN KONSELING DI MADRASAH DAN SEKOLAH - Muhammad Munadi; Suwarta Suwarta (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2020)
This study will examine the development of spirituality through guidance and counseling services in madrasas and schools. The research method used document studies on the development of spirituality in schools and madrasas. The Independent Student Competency Standard Document (SKKPD) is taken from the Operational Guidance for the Implementation of Guidance and Counseling for Junior High Schools (SMP) and Senior High Schools (SMA) published by the Directorate General of Teachers and Education Personnel of the Ministry of Education and Culture in 2016 by juxtaposing Basic Competency Competency Standards ( SKKD) in Islamic Religious Education Subjects. Data analysis using descriptive qualitative analysis. The results showed that the development of spirituality in the junior and senior high school level refers to the SKKPD for SMP and SMA and is in line with the Competency Standards for the Subject Group (SKKMP) for the subjects of Islamic Religious Education at that level